Accumulation and phytotoxicity of perfluorooctanoic acid in the model plant species Arabidopsis thaliana. (November 2015) - Yang, Xinping; Ye, Chengchen; Liu, Yu; Zhao, Fang-Jie
Abstract: Perfluorooctanoic acid (PFOA) is widely used in the manufacture of many industrial and household products. To assess the potential environmental risk of PFOA, its accumulation, translocation and phytotoxic effects were investigated using the model plant species Arabidopsis thaliana . Exposure to 18 μM PFOA-F in agar plates did not affect plant growth, but 181–1811 μM PFOA-F inhibited root and shoot growth. PFOA was more phytotoxic on shoot growth than NaF at the equivalent F concentration, with the latter having 3.9–7.6 times higher EC50 for shoot biomass than PFOA. PFOA was efficiently translocated from roots to shoots, where it existed as intact PFOA molecules without transformation evidenced by the 19 F NMR spectra. PFOA caused a significant increase in the concentration of H2 O2 and malondialdehyde (MDA) in shoots, indicating that oxidative stress is a likely cause of PFOA phytotoxicity. Graphical abstract: Highlights: PFOA is more phytotoxic on shoot growth than NaF at the equivalent F concentration. PFOA is readily taken up and translocated from roots to shoots. PFOA exists as intact molecules without transformation in Arabidopsis shoots. PFOA causes oxidative stress in Arabidopsis shoots. Abstract : Perfluorooctanoic acid causes oxidative stress and is more phytotoxic on shoot growth than inorganic fluoride at the equivalent F concentration.